1982
DOI: 10.1111/j.1348-0421.1982.tb00209.x
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Composition of Lipopolysaccharides of Family Vibrionaceae

Abstract: A comparative study was carried out on the sugar composition of lipopolysaccharides (LPS) isolated from representative strains of members of the family Vibrionaceae including all of the constituting genera, i.e., Vibrio, Aeromonas, Photobacterium, Plesiomonas, and Lucibacterium. More than 100 strains were examined. It was found that, with the exception of Vibrio parahaemolyticus 06, 2-keto-3-deoxyoctonate (KDO), known generally as a component sugar in the core region of usual gram-negative bacterial LPS, is vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The sugar composition of the O-antigenic lipopolysaccharides (LPS) isolated from all 12 has been determined (5)(6)(7)18). On the basis of the sugar composition, LPS of the 12 of V. parahaemolyticus was divided into nine chemotypes, because O3, O5 and O11 LPS belong to the same chemotype and O7 and 012 LPS to another chemotype (5,9).…”
mentioning
confidence: 99%
“…The sugar composition of the O-antigenic lipopolysaccharides (LPS) isolated from all 12 has been determined (5)(6)(7)18). On the basis of the sugar composition, LPS of the 12 of V. parahaemolyticus was divided into nine chemotypes, because O3, O5 and O11 LPS belong to the same chemotype and O7 and 012 LPS to another chemotype (5,9).…”
mentioning
confidence: 99%
“…Although most LPSs reported so far contain KDO it is known that Vibrio cholerae LPS lacks KDO (10 , 11). Recently, it was reported that the LPSs of most of the family Vibrionaceae also lack KDO (9). We also reported that LPSs from several marine photobacteria belonging to the family Vibrionaceae had undetectable or only small amounts of KDO in their constituents (12,13).…”
mentioning
confidence: 75%
“…KDO was estimated by the method of Weissbach & Hurwitz (1959). Degraded polysaccharide (DPS) was prepared from the supernatant of a weak-acid hydrolysate (S% acetic acid, 100 "C, 3 h) of LPS (Hisatsune et al, 1985). Gel chromatography was performed with Sephadex G-50 and G-10 columns (1.6 x 100 cm) using pyridine/acetic acid/water (10 :4: 1000, by vol.)…”
Section: Methodsmentioning
confidence: 99%
“…In the elution profiles of 'DPS' of either Ogawa or Inaba LPS in Sephadex G-50 gel chromatography using pyridine/acetate buffer (pH 7.0) as eluent (Hisatsune et al, 1985), typically three peaks are observed : the first peak (fraction I) corresponds to the polymeric 0-polysaccharide side chain, namely an a( 1 +2)-linked homopolymer of perosamine, with the attached core stubs, the second peak (fraction 11) to the core oligosaccharide, and the third peak (fraction 111) to low-molecular-mass fragments, namely fructose and inorganic phosphate. Sephadex G-50 gel filtration of 'DPS' prepared from either Ogawa or Inaba 'oxidized LPS' was carried out.…”
Section: Efect Of Periodate Oxidation On Chemical Structure Of Lpsmentioning
confidence: 99%